Optical and Structural Properties of SnO2 Thin Films Prepared by Sputtering Method - Haza’a, S. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
SnO2 thin films of different two thicknesses were prepared an glass substrate by DC magnetron sputtering. The crystal structure and orientation of the films were investigated by XRD patterns. All the deposited films are polycrystalline. The grain size was calculated as 25.35, 28.8 nm. Morphological and compositions of the films were performed by SEM and EDX analyses respectively. The films appeared compact and rougher surface in nature. The allowed direct band gap was evaluated as 3.85 eV, and other optical constants such as refractive index, extinction coefficient, real and imaginary parts of dielectric constants were determined from transmittance spectrum in the wavelength range (300-900) nm and also analyzed.